Implementation of the Suggestion-Imagination Method in Learning to Write Short Story Texts for Grade XI Students - Rumiati, Rumiati; Wahab, Abd Aziz; Ahnaf, Fatih Holis (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
This study aims to describe the implementation of the suggestion-imagination method in teaching short story writing to students at SMA Sirojul Arifin. The background of this research is the low ability of students to develop imagination and creative ideas in writing short stories. This study uses a descriptive qualitative method with observation, interview, and documentation techniques. The results show that the suggestion-imagination method stimulates students' imagination and creativity, making it easier for them to express their ideas in the form of short story texts. Moreover, students demonstrated high enthusiasm and improvement in writing quality after the application of this method. Therefore, the suggestion-imagination method is effective in enhancing students' short story writing skills.